E-guerrilla 3D participation: Approach, implementation, and usability study - Chassin, Thibaud; Ingensand, Jens (Frontiers in Virtual Reality, 2022)
Typical urban participatory approaches engage citizens through lengthy sessions far from the area under transformation by an urban project. Several issues result from these settings of involvement including the mobilization of similar individuals, overwhelming participatory codes, or a gap between the affected urban landscape and the location of the session. This study introduces a modern approach that leverages the use of 3D web applications to address some of the critical challenges of popular participatory sessions. The developed approach, named e-guerilla 3D participation, is based on five dimensions: immediate participation, ease of use, flexibility, place-based engagement, and immersivity. A prototype complying with these five dimensions was implemented in this study. The prototype promotes an in situ engagement where all the users (without distinction) of a public area can explore a future urban project and get involved within minutes. A usability study conducted with 26 expert and non-expert participants investigated the prototype through a fictive scenario. The findings demonstrate a positive outcome in terms of participatory results that are identifiable with the prototype (highlighting the controversial elements of the projects) and encourage feedback collected during a survey and interview. The usability study suggests key aspects that should be considered to improve the design of participatory sessions and their interactive mediums (or tools), such as realism, affordance, incentive, and purpose. The promising participatory approach (and prototype), which was unpacked step-by-step in this study, does not replace typical practices but could help to complement them by reaching a non-selected and broader public; hence leading to the design of more inclusive participatory approaches.